Shoot organogenesis from leaf discs of the African ginger (Mondia whitei (Hook.f.) Skeels), an endangered medicinal plant - Patricia, Driciru; Stephen, Buah; John, Adriko (In Vitro Cellular & Developmental Biology-Plant, 2021)
The African ginger (Mondia whitei) is an endangered, endemic African medicinal plant, widely used as an aphrodisiac and to manage gastrointestinal problems and anorexia. Due to high demand, it is over-utilized from the wild without replenishment and destroyed by inappropriate harvesting methods. Therefore, there is a need to develop an efficient conservation system for the African ginger. This study focused on developing an in vitro propagation procedure for the African ginger through indirect shoot organogenesis. Optimal callus formation was induced from leaf explants cultured on Murashige and Skoog (MS) basal medium fortified with 1.5 mg L−1 2,4-dichlorophenoxyacetic acid (2,4-D). The 1.5 mg L−1 6-benzylaminopurine (BAP) concentration was optimal with 50% of the callus-forming buds. For shoot formation, media with 2.0 mg L−1 BAP and 1.0 mg L−1 NAA resulted in 60% of the buds developing shoots. Regenerated shoots were rooted on woody plant medium (WPM) fortified with 0.1 mg L−1 BAP and no rooting hormone included. The survival rate of weaned and acclimatized plants was 70% and up to 80% respectively. The study demonstrates an in vitro propagation route for the African gingerwhich could support itsmass production for medicinal use, availing of planting materials, conservation, and commercialization purposes.
Keywords: Regeneration; In vitro propagation; Conservation; Organogenesis